KENAKALAN REMAJA DI DESA SUNGAI PAKU (Studi Kasusus SMP 4 Kampar Kiri Kabupaten Kampar) - Winda Oktawati; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research has been held in Sungai Paku Village, with case study Junior High School 4th Kampar Kiri in Kampar resident. The problem was examined is the cause of juvenile delinquency whom made social unrest in people society, the kind of juvenile delinquency. The goal is to know the cause of juvenile delinquency and to know the kind of it. Researcher the 5 (five) persons into research as samples, they are is the actor of the juvenile delinquency and also as provocateur. The researcher use deviation theory, social act theory, and social control theory. The writer use qualitative descriptive, that describe the phenomenon in the field who matching with actual events using procedure problem solving base on reality. And also use Accidental sampling technique, that is take the samples with considerations who will be give the maximal information. From the result of research the kind of juvenile delinquency are steal, drug users, crystal meth, liqour, and free sex.They are together steal and the money use for buy drugs, crystal meth and liqour then the rest they devide. The cause of juvenile delinquency is lack of supervision and attention from their parents and environment impact to their grow up process, they have no relion values and decency where they are being grow up.Keyword: juvenile delinquency, teenager, Deviation